PENGARUH PENANAMAN MODAL DAN KETERBUKAAN EKONOMI TERHADAP PERTUMBUHAN EKONOMI - Zahroti, Puji Aisyah; Juliprijanto, Whinarko (Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa); Vol 7 No 2 (2022): Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa), 2022)
There are various factors both from within and outside the country that can affect the economic growth of a country. This study aims to analyze the effect of investment and economic openness on economic growth. The GDP variable represents economic growth, the investment variables used are FDI and GFCF. The variables of economic openness used are exports and imports. The data used is secondary data from the website of World Bank from 1991 to 2020. The data is processed using ECM followed by classical assumption test to find out the model used is Best Linear Unbias Estimation (BLUE). The results showed that in the long term and short term FDI had no significant effect on economic growth. While other variables are GFCF, exports and imports in the short and long term have a significant effect on economic growth.